(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Learning an international language presents unique challenges and attitudes for speakers of other native tongues. This article explores the difficulties faced, perceptions held, and suggestions offered by non-native learners of globally prevalent languages like English, Mandarin, Spanish, and Arabic. Through a comprehensive literature review, common threads are identified regarding linguistic barriers, motivational factors, optimal teaching methodologies, and sociocultural considerations.